Peran pemaafan sebagai mediator hubungan antara kebersyukuran dan kebahagiaan pada remaja di panti asuhan - MEILIANAWATI, MEILIANAWATI; Iswinarti; Muhammad Salis Yuniardi (Psychological Journal: Science and Practice, 2024)
Abstract Happiness is everyone’s need, therefore everyone wants it, including teenagers in orphanages. Happinessis related to gratitude, teenagers in orphanages who have a high level of gratitude will have a high level of happiness.Likewise, teenagers in orphanages who have a high level of gratitude will have a high level of forgiveness. Teenagers inorphanages who forgive tend to be happier than teenagers who don’t forgive. The purpose of this study was to determinethe role of forgiveness as a mediator in the relationship between gratitude and happiness in adolescents in orphanages.This study uses a quantitative approach. Subjects were determined through a saturation sampling technique consistingof 100 teenagers at an orphanage in Malang City. The research instrument uses The Gratitude Questionnaire-SixItemForm (GQ-6), the Heartland forgiveness scale and the Indonesian version of The PERMA-Profiler scale. Mediationanalysis using Process model 4 by Hayes. The results show that gratitude has a positive and significant relationship tohappiness. The results of this study also prove that forgiveness is able to mediate the relationship between gratitude andhappiness with a value.The conclusion from the results of this study forgiveness can be a mediator of the relationshipbetween gratitude and happiness in adolescents in orphanages